Online Reviews, Trust, and Booking Intention: Airbnb Villas in Seminyak - Ni Komang Ayu Wandira; I Putu Utama; I Gusti Agung Gede Witarsana (LP2M IAIN Palopo, 2025)
This study investigates the mediating role of trust in the relationship between online reviews and booking intention for Airbnb villas in Seminyak, Bali. A quantitative descriptive approach was applied using questionnaires distributed to 140 Airbnb users who had previously booked villas in the area. Data were analyzed through Structural Equation Modeling (SEM) using the Partial Least Squares (PLS) technique in SmartPLS 4 to test direct and indirect relationships. The results indicate that online reviews significantly influence user trust but do not directly affect booking intention, while trust alone also shows no significant effect on booking intention. However, when tested as a mediating variable, trust successfully connects online reviews to booking intention. This implies that online reviews can enhance booking intention only by first strengthening user trust. Practically, the findings emphasize the importance for Airbnb managers and accommodation providers to ensure credible and transparent reviews as a strategy to build trust and encourage confident booking decisions.